Fertility - preserving treatment strategies for adult and pediatric malignancies - current state of knowledge - Bogdan , Klaudia; Jankowski, Mikołaj; Janicka, Urszula; Ciepluch, Natalia; Słomiński, Szymon; Toczek, Wiktoria (Quality in Sport, 2025)
Introduction and purpose: The global incidence of malignant tumors is rising, including among young adults who may not yet have considered parenthood. While improved oncological treatments have increased survival rates, they often carry the risk of gonadotoxicity, leading to infertility. This growing challenge has contributed to the development of oncofertility - an interdisciplinary field combining oncology, reproductive medicine, endocrinology, embryology, psychology, and ethics. This article aims to review current literature, highlight recent advances, and discuss available fertility preservation strategies for cancer patients. Material and methods: A literature review was conducted using PubMed, Embase, and Google Scholar databases with relevant keywords. State of knowledge: Fertility preservation is feasible in many oncology patients, provided it is discussed prior to initiating treatment. Informed consent, particularly for minors, must involve guardians. For postpubertal males, sperm cryopreservation is the standard; testicular tissue preservation remains experimental, especially in prepubertal boys. Female patients have more options: oocyte or embryo cryopreservation are preferred, depending on partner status and treatment timeline. Ovarian tissue cryopreservation, though still experimental in children, is an option. Ovarian transposition before radiotherapy and hormonal protection are considered complementary approaches. Conclusions: Cancer therapies can significantly impair reproductive function, affecting quality of life. Despite rapid advances in oncofertility, no method guarantees future fertility. Early patient education and individualized care are essential to maximizing reproductive outcomes post-treatment.